EFFECT OF SUPPLEMENTATION WITH DRIED DILL POWDER (ANETHUM GRANVEOLENS L.) IN DIET ON SOME BLOOD CHARACTERISTICS OF BROILED CHICKENS - Ali, H. A. M. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2016)
This study was conducted to investigate the effect of supplementation different levels of dried dill powder with diet on some physiological characteristics of  broiler chickens. 336 chicks, day-old 46 gm weight /chick. Birds were randomly distributed into four treatment groups with three replicates per treatment (28 bird/replicate).Treatments were as follow:T1: control group (without any addition) T2, T3 and T4 adding dried dill powder at levels  0.4 ,0.6, 0.8% respectively. Experiment lasted five weeks, which at the end measurements of protein, glucose, albumin, uric acid, cholesterol, triglycerides, high density lipoprotein (HDL), low density lipoprotein (LDL) and very low density lipoprotein (VLDL) in blood serum were done. The results showed  a significant (p